2012
DOI: 10.1002/14651858.cd004882.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Chinese herbs combined with Western medicine for severe acute respiratory syndrome (SARS)

Abstract: Background Severe acute respiratory syndrome (SARS) is an acute respiratory disease caused by a novel coronavirus, which first appeared in Foshan City, China on 22 December 2002. Chinese herbs were used in its treatment. Objectives To evaluate the possible e ectiveness and safety of Chinese herbs combined with Western medicines versus Western medicines alone for SARS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
92
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(96 citation statements)
references
References 10 publications
0
92
0
4
Order By: Relevance
“…Severe acute respiratory syndrome (SARS) first appeared in 2002 in China. In mainland China about 50% of patients were treated with Chinese herbal medicine as an adjunct therapy in addition to Western medicine (see ), and some positive effects in SARS patients had been reported (see (Liu et al, 2008)). By screening a large number of Chinese herbs (Ho et al, 2007) emodin was identified as an effective component of Polygonaceae to block the interaction of the SARS-coronavirus spike protein (SARS-CoV S protein) with the angiotensin-converting enzyme 2 (ACE2) and to reduce the infection by S protein-pseudo-typed retrovirus.…”
Section: Introductionmentioning
confidence: 99%
“…Severe acute respiratory syndrome (SARS) first appeared in 2002 in China. In mainland China about 50% of patients were treated with Chinese herbal medicine as an adjunct therapy in addition to Western medicine (see ), and some positive effects in SARS patients had been reported (see (Liu et al, 2008)). By screening a large number of Chinese herbs (Ho et al, 2007) emodin was identified as an effective component of Polygonaceae to block the interaction of the SARS-coronavirus spike protein (SARS-CoV S protein) with the angiotensin-converting enzyme 2 (ACE2) and to reduce the infection by S protein-pseudo-typed retrovirus.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated remarkable beneficial actions of luteolin through its anti-inflammatory activity. The research of modern scientists has shed new light on honeysuckle in the treatment of SARS and H1N1 influenza [13][14][15] . Luteolin protects mice against LPSinduced toxicity, alleviates bronchoconstriction and airway hyperreactivity in ovalbumin-sensitized mice, and decreases Chlamydia pneumoniae infection-induced inflammatory reactions [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…There are several convincing arguments for integration of these disparate systems of medicine. Integration is already helping patients with many chronic diseases [3,4], severe acute respiratory syndrome (SARS) [5], AIDS [6] and etc. Moreover, integration would be more economical for the health care system [7].…”
Section: Introductionmentioning
confidence: 99%